Quantitative in vivo assessment of intraocular lens calcification: correlation between OCT opacity and straylight measurement - Mackenbrock, Lars; Łabuz, Grzegorz; Henningsen, Nikola; Auffarth, Gerd U.; Khoramnia, Ramin; Yildirim, Timur Mert (Journal of cataract and refractive surgery, 2025)
Purpose: - To quantitatively assess intraocular lens (IOL) calcification using anterior segment optical coherence tomography (AS-OCT) and correlate findings with straylight measurements in patients with homogenous IOL calcification. - Setting: - Department of Ophthalmology, Heidelberg University Hospital, Heidelberg, Germany. - Design: - Prospective, observational clinical study. - Methods: - Healthy patients with homogenous IOL calcification underwent AS-OCT imaging with the ANTERION, with IOL opacity being automatically quantified using a custom image-analysis script. Straylight was assessed using the C-Quant straylight meter. Correlation between IOL opacity and straylight was analyzed using Spearman ρ coefficient. - Results:  - 35 eyes of 35 patients (mean age 72.9 ± 7.8 years) were included. Mean IOL opacity was 69.15 ± 13.55 pixel intensity units (PIUs), and mean straylight was 2.24 ± 0.38 log(s). A statistically significant correlation was found between IOL opacity and straylight with ρ = 0.494, P = .003. After the linear regression model was established: straylight = 0.0569 × OCT opacity [log(s)] − 1.69 with R2 = 0.244. Of the 35 eyes, 17 underwent IOL exchange surgery, with a mean IOL opacity of 75.69 ± 7.58 PIU and a mean straylight of 2.33 ± 0.30 log(s). - Conclusions: - AS-OCT can quantitatively assess IOL calcification in vivo, with results correlating significantly with straylight measurements. This technique may serve as a valuable diagnostic tool for evaluating IOL opacification and assist in surgical decision-making, particularly in borderline cases.
Gesehen am 16.01.2026